2020
DOI: 10.1177/1073858420975711
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids in the Physiological and Transcriptional Regulation of 5-HT1A Receptor and the Pathogenesis of Depression

Abstract: There is growing increase in the global prevalence of depression, but treatment outcome of this highly disabling disease is not satisfactory. Many patients are not benefitted by the currently prescribed antidepressants—together with this partial remission is very common. Improving treatment strategies and developing better therapeutic agents for treating depression is therefore highly needed. Stress-related epigenetic changes play a critical role in the pathogenesis as well as treatment of depression. Stressfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…Nevertheless, we have decided to leave these factors in a separate category (because their categorization may not be as immediately clear-cut as others), and these factors include: low-level light [ 429 ], weight cycling [ 430 ], water contaminants [ 431 ], trade [ 432 ], air pollution [ 433 , 434 ], program-level variables (ex. feedback and learning experience) [ 435 ], TV viewing [ 436 ], falls [ 437 ], various other biological factors [ 116 , 136 , 141 , 151 , 164 , 182 , 363 , 364 , 438 , 439 , 440 , 441 , 442 , 443 , 444 , 445 , 446 , 447 , 448 , 449 , 450 , 451 , 452 , 453 , 454 , 455 , 456 , 457 , 458 , 459 , 460 , 461 , 462 , 463 , 464 , 465 , 466 , 467 , 468 , …”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, we have decided to leave these factors in a separate category (because their categorization may not be as immediately clear-cut as others), and these factors include: low-level light [ 429 ], weight cycling [ 430 ], water contaminants [ 431 ], trade [ 432 ], air pollution [ 433 , 434 ], program-level variables (ex. feedback and learning experience) [ 435 ], TV viewing [ 436 ], falls [ 437 ], various other biological factors [ 116 , 136 , 141 , 151 , 164 , 182 , 363 , 364 , 438 , 439 , 440 , 441 , 442 , 443 , 444 , 445 , 446 , 447 , 448 , 449 , 450 , 451 , 452 , 453 , 454 , 455 , 456 , 457 , 458 , 459 , 460 , 461 , 462 , 463 , 464 , 465 , 466 , 467 , 468 , …”
Section: Resultsmentioning
confidence: 99%
“…According to Carr et al., mice with a higher density of 5-HT 1A autoreceptors demonstrated enhanced responses to stressors. In addition, it is suggested that synthetic compounds with antagonist activity for glucocorticoid receptors and agonist activity for 5-HT 1A receptors may prove better therapeutic agents for treating depression . Consequently, drugs such as buspirone, a partial agonist for 5-HT 1A receptors, are used clinically to treat mood disorders such as depression and anxiety …”
Section: Resultsmentioning
confidence: 99%
“…In addition, it is suggested that synthetic compounds with antagonist activity for glucocorticoid receptors and agonist activity for 5-HT 1A receptors may prove better therapeutic agents for treating depression. 37 Consequently, drugs such as buspirone, a partial agonist for 5-HT 1A receptors, are used clinically to treat mood disorders such as depression and anxiety. 38 Results indicated the possible modulation of 5-HT 2A receptors by SeBZF3 since its antidepressant-like effect was impeded by ketanserin, a 5-HT 2A/C receptor antagonist.…”
Section: Involvement Of 5-ht 1a 5-ht 2a/2c and 5-htmentioning
confidence: 99%
“…Adrenocortical steroids enter the brain and have widespread effects, particularly impairing hippocampal function ( 86 ). Long-term exposure to the hormone environment can decrease the secretion of derived neurotrophic factor (BDNF) and interfere with neural development ( 87 , 88 ). Adrenocortical hormones not only destroy the plasticity and structure of neurons, but also exert cytotoxic effects by regulating neurotransmitters.…”
Section: Graves' Disease As a Mechanistic Driver Of Depressionmentioning
confidence: 99%